Self-image addiction (Salafi) and its relation to narcissistic personality disorder among students (Journal Of Educational and Psychological Researches, 2018)
Abstract The goal of current study was to identify the relationship between addiction of self-images (Selfie) and personality disorder of narcissus, and the difference of significance the relationship between addiction self-images (selfie) and personality disorder narcissus at students of Mustansiriya university, addiction self- images (selfie) defined: a photograph that one has taken of oneself, typically one taken with a smartphone or webcam and shared via social media, edit and down lowed to social networking sites, and over time, the replacement of normal life virtual world, which is accompanied by a lack of a sense of time, and the formation of repeated patterns increase the risk of social and personal problems. To achieve the goals of current study, the researcher building two scales, first to identify the addiction of self-image, second and personality disorder of narcissus, the participants were (400) students from Al-Mustansiriya University. The results of current study were the significant statistically correlation between addiction self-images (selfie) and narcissistic personality disorder. The current study has reached a number of future study and recommendations.